Improved Convolutional Neural Network for Chinese Sentiment Analysis in Fog Computing. (23rd September 2018) - Chen, Haoping; Du, Lukun; Lu, Yueming; Gao, Hui
Abstract : Fog computing extends the concept of cloud computing to the edge of network to relieve performance bottleneck and minimize data analytics latency at the central server of a cloud. It uses edge nodes directly to perform data input and data analysis. In public opinion analysis system, edge nodes that collect opinions from users are responsible for some data filtering jobs including sentiment analysis. Therefore, it is crucial to find suitable algorithm that is lightweight in operation and accurate in predictive performance. In this paper, we focus on Chinese sentiment analysis job in fog computing environment and propose a non-task-specific method called Channel Transformation Based Convolutional Neural Network (CTBCNN) for Chinese sentiment classification, which uses a new structure called channel transformation based (CTB) convolutional layer to enhance the ability of automatic feature extraction and applies global average pooling layer to prevent overfitting. Through experiments and analysis, we show that our method do achieve competitive accuracy and it is convenient to apply this method to different cases in operation.